2016
DOI: 10.1051/matecconf/20166600016
|View full text |Cite
|
Sign up to set email alerts
|

Provisions of Disabled Facilities at The Malaysian Public Transport Stations

Abstract: Abstract. Public transport stations need to provide access and facilities for people with disabilities (PWD) in fulfilling the requirements of the Malaysian Standard Code of Practice on Access of Disabled Persons (MS). However, most public transport stations in Malaysia are reported as still lacking in terms of providing good designs and facilities for the PWDs. This inaccessible environment affects the PWDs to negatively participate in the social and economic mainstream. The research aims at identifying the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 3 publications
2
10
0
Order By: Relevance
“…[28,29] In spite of many advantages of drive-through services, it is important to note that this service would be of maximum benefit for citizens who own a vehicle and when the hospital is faced with inadequate car parks. [30][31][32][33] Respondents expect pharmacy staff to be more polite and courteous. Evidence showed that pharmacist attitude is positively correlated with patient satisfaction visiting pharmacy department of public hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…[28,29] In spite of many advantages of drive-through services, it is important to note that this service would be of maximum benefit for citizens who own a vehicle and when the hospital is faced with inadequate car parks. [30][31][32][33] Respondents expect pharmacy staff to be more polite and courteous. Evidence showed that pharmacist attitude is positively correlated with patient satisfaction visiting pharmacy department of public hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…As stipulated by several local researchers (Hussein et al, 2012;Kadir et al, 2012;Kamarudin et al, 2012;Mohd Isa et al, 2016) the MS1183:1990MS1184:1991and MS1331:1993, are the code of practice for fire precautions, access to buildings and access outside buildings for PwDs. Evidence of awareness and technical knowledge of providing accessibility for PwDs is the obligatory responsibility of using MS code of practice stated above, in detailed design for PwDs design requirements.…”
Section: Issues and Problemmentioning
confidence: 99%
“…In terms of facility, the accessibility measurement can be categorized into two aspects. First, objective measurement (a checklist) has been used in various studies (Dickson et al, 2016;Isa et al, 2016;Rimmer et al, 2016;Sáa et al, 2012;Talib et al, 2016). Second, subjective measurement (a questionnaire) which allows participants to rate items from their perception has also been applied in prior studies (Bodaghi & Zainab, 2012;Pratiwi et al, 2015;Sang et al, 2016;Tutuncu, 2017).…”
Section: Measurements Of Accessibilitymentioning
confidence: 99%
“…In this study, accessibility is defined as the ease of reaching a sport facility and performing the functions at different stages of a journey (Alagappan, Hefferan, & Parivallal, 2017;El-Geneidy & Levinson, 2006). Based on previous literature, most studies capture accessibility in one stageaccessibility within the destination (Bodaghi & Zainab, 2012;Isa, Zanol, Alauddin, & Nawi, 2016;Pratiwi, Zhao, & Mi, 2015;Rimmer, Padalabalanarayanan, Malone, & Mehta, 2016;Sáa, Azevedob, Martins, Machadob, & Tavaresb, 2012;Talib, Ghani, Ismail, & Salleh, 2016;Tutuncu, 2017). Our study argues that accessibility should be explored as a whole journey (multiple stages).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation